1987
DOI: 10.1128/jvi.61.4.1007-1018.1987
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in nuclear matrix structure after adenovirus infection

Abstract: Infection of HeLa cells with adenovirus serotype 2 causes rearrangements in nuclear matrix morphology which can best be seen by gentle cell extraction and embedment-free section electron microscopy. We used these techniques to examine the nuclear matrices and cytoskeletons of cells at 6, 13, 28, and 44 h after infection. As infection progressed, chromatin condensed onto the nucleoli and the nuclear lamina. Virus-related inclusions appeared in the nucleus, where they partitioned with the nuclear matrix. These v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…We have also seen nuclear filaments in adenovirus-infected HeLa cells (Zhai et al, 1987) as chromatin retracts, leaving filaments uncovered. At later stages of adenovirus infection these filaments are decorated with adenovirus nucleocapsids.…”
Section: Discussionmentioning
confidence: 60%
“…We have also seen nuclear filaments in adenovirus-infected HeLa cells (Zhai et al, 1987) as chromatin retracts, leaving filaments uncovered. At later stages of adenovirus infection these filaments are decorated with adenovirus nucleocapsids.…”
Section: Discussionmentioning
confidence: 60%
“…Additionally, recent EM studies on the nuclear matrix architecture of Ad2-infected HeLa cells (21) indicated that Ad2 capsids throughout the nucleus were associated with each other and the nuclear envelope by filaments. From all these data we suggest that Ad2 DNA replication sites are associated with the nuclear envelope but that the replicated DNA can be extended into the nuclear interior as it is 'reeled through' fixed replication sites (reviewed in 1).…”
Section: Intranuclear Localization Of Ad2 Dna In Hela Cellsmentioning
confidence: 99%
“…Output of the equipment and sonic treatment time of the cells were determined by EM detecting of the effect of the second extraction (usually 'Output control' 2.5 for 2 min was suitable for 10 mL cells in CSK at 2.0 x 10 6 cells/mL). The sequential extractions were performed as described by Zhai et al (1987) with some modifications. Briefly the steps are as follows: 1) sonicated cells were collected by centrifugation (600 g, 5 min) and suspended in CSK-Triton buffer (CSK buffer containing 0.5% (vol/vol) Triton X-100) and extracted for 5 min at 0°C.…”
Section: Sequential Cell Extractionsmentioning
confidence: 99%